International exchange of genetic resources, the role of information and implications for ownership: the case of the U.S. National Plant Germplasm System - Day-Rubenstein, Kelly; Smale, Melinda (International Food Policy Research Institute, 2004)
Changing perceptions of resource ownership have altered international exchange of genetic resources. After summarizing the role of genebanks and issues related to property regimes, this paper presents an empirical study of one of the largest national genebanks, the U.S. National Germplasm System. The demand for its genetic resources appears to be substantial, both domestically and internationally. Utilization rates are higher than suggested by past studies. The role of information in enhancing the usefulness of NPGS resources is explored with an econometric model that indicates that accompanying data make germplasm more useful. U.S. requestors account for most of the germplasm demanded, but developing countries appear to make greater use of these resources, proportionally, in terms of overall usefulness, secondary sharing, and the presence of useful data. Demand for public germplasm is likely to increase in the future, particularly from developing countries. -- Authors' Abstract